A refined method for theory-based evaluation of the societal impacts of research - Belcher, B.; Davel, R.; Claus, R. (Elsevier, 2020)
With high and increasing expectations for research to have social and environmental impact, there is a corresponding need for appropriate methods to demonstrate (for accountability) and analyze (for learning) whether and how research projects contribute to change processes. Evaluation is especially challenging for problem-oriented research that employs inter- and transdisciplinary approaches and intervenes in complex systems, where experimental and statistical approaches to causal inference are inappropriate. Instead, theory-based evaluation can be applied to identify and test causal processes. This paper presents a detailed explanation of the Outcome Evaluation approach applied in Belcher et al. (2019b). It draws on concepts and approaches used in theory-based program evaluation and the more limited experience of theory-based research evaluation, providing a brief overview of conceptual strengths and limitations of other methods. The paper offers step-by-step guidance on application of the Outcome Evaluation approach, detailing how to: document a theory of change; determine data needs and sources; collect data; manage and analyze data; and present findings. This approach provides a clear conceptual and analytical framework in addition to actor-specific and impact pathway analyses for more precision in the assessment of outcomes. Specifically, the Outcome Evaluation approach: •Conceptualizes research within a complex system and explicitly recognizes the role of other actors, context, and external processes;•Utilizes a detailed actor-centred theory of change (ToC) as the analytical framework; and•Explicitly tests a set of hypotheses about the relationship between the research process/outputs and outcomes.